Návrh implementace systému řízení vztahů se zákazníky - Oškrdová, Petra (Vysoké učení technické v Brně. Fakulta podnikatelská, 2009)
Tato diplomová práce se zabývá návrhem zlepšení a možnosti širšího využití databázového softwaru pomocí CRM systému pro již existující zahraniční firmu, která má svoji pobočku v České republice. Ve firmě je současný databázový systém nedostačující. Je potřeba navrhnout nový, se kterým se bude pracovat mnohem efektivněji.

This diploma thesis is concerned with proposal and analysis new database software helping by CRM system for already exists foreign company, which has own branch office in Czech Republic. There is current database system deficient in the company. There is necessary to propose the new software, which will be operating more effectively.
Proposal of Customer Relationship Management Implementation
Keywords: CRM (Customer Relationship Management); Siebel Systems; zákazník; databáze; software; IT (informační technologie); CRM (Customer Relationship Management); Siebel Systems; customer; database; software; IT(information technology)